Assessment of Knowledge Among the Physicians Regarding Dental Screening Prior to Chemotherapy and Radiotherapy - Khalid Gufran; Rama Alyamany; Abdullah Saad Alqahtani; Bassel Tarakji; Linah Ibrahim Alzughaibi; Meshal Mohammed Alhaqbani; Saeed Abdullah Basalem (Association of Support to Oral Health Research (APESB), 2023)
Objective: To evaluate the physicians' knowledge regarding the referral for dental screening prior to chemotherapy and radiotherapy. Material and Methods: We conducted a cross-sectional study using simple random sampling among 468 physicians from various specialties with diverse experience levels from different regions in Saudi Arabia. A self-reporting questionnaire was distributed among the physicians, which consisted of questions assessing the physicians' knowledge about oral health and complications in patients prior to chemotherapy and radiotherapy. Statistical analysis was done after the data was collected employing SPSS, and p<0.05 was taken as significant. Results: Residents were more as expected (39.3%), followed by specialists (2.31%). The majority had a practice experience for more than five years (67.8%). The scores for the knowledge assessment showed that 51.3%, nearly half of the participants, had lower scores. The scores were statistically significant (p<0.05). Conclusion: General physicians and specialists should be aware of the dental complications and associated diseases in patients with malignancies and those undergoing chemo and radiotherapy. It is proposed that more awareness should be raised among physicians to rectify this lapse.